Giant infiltrating angiolipoma of buccal space—Report of a rare case. Issue 2 (March 2020) - Shetty, Nisha; Kudva, Adarsh; Kamath, Abhay T.; Mathew, Mary; Solomon, Monica Charlotte
Abstract: Angiolipoma is an histological subtype of lipoma that arise from adipose tissue. They occur in trunk and extremities more commonly and are rarely found in the maxillofacial area. Infiltrating and non-infiltrating types are the two subtypes of Angiolipoma, and they have a marked degree of vascularization with an admixture of mature adipocytes. The infiltrating type is rare in head and neck regions and should be considered in the differential diagnosis of head and neck lesions as it infiltrates into surrounding structures causing muscular pain and nerve deficits and also has a high rate of recurrence. Management of angiolipomas requires complete surgical excision. In this report, we present a case of a Giant Infiltrating Angiolipoma in Buccal Space of a 51-year-old man.